The Influence of interpersonal communication, work environment, and job satisfaction on job loyalty employees of PT. Tamtama Mulia Abadi - Naibaho, Togar; Naibaho, Winfrontstein (Institute of Computer Science (IOCS), 2024)
This study aims to determine and analyze the effect of interpersonal communication, work environment, and job satisfaction on employee loyalty of PT Tamtama Mulia Abadi. The type of research is associative analysis. Based on the results of the t hypothesis test, it can be concluded that partially interpersonal communication has a significant effect on work loyalty, work environment has a significant effect on work loyalty, job satisfaction has a significant effect on work loyalty. Based on the results of the F hypothesis test, it can be concluded that simultaneously interpersonal communication, work environment, and job satisfaction have a significant effect on job loyalty. Based on the results of the coefficient of determination, the coefficient of determination or Adjusted R-Square is 0.454 or 45.4%, which means that the effect of interpersonal communication, work environment, and job satisfaction on job loyalty is 45.4%, while the remaining 54.6% is influenced by other variables or factors not examined